The implementation of a mobile problem-specific electronic CEX for assessing directly observed student–patient encounters - Gary S. Ferenchick; Jami Foreback; Basim Towfiq; Kevin Kavanaugh; David Solomon; Asad Mohmand (Medical Education Online, 2010)
Background: Facilitating direct observation of medical students' clinical competencies is a pressing need. Methods: We developed an electronic problem-specific Clinical Evaluation Exercise (eCEX) based on a national curriculum. We assessed its feasibility in monitoring and recording students' competencies and the impact of a grading incentive on the frequency of direct observations in an internal medicine clerkship. Students (n=56) at three clinical sites used the eCEX and comparison students (n=56) at three other clinical sites did not. Students in the eCEX group were required to arrange 10 evaluations with faculty preceptors. Students in the second group were required to document a single, faculty observed ‘Full History and Physical’ encounter with a patient. Students and preceptors were surveyed at the end of each rotation. Results: eCEX increased students' and evaluators' understanding of direct-observation objectives and had a positive impact on the evaluators' ability to provide feedback and assessments. The grading incentive increased the number of times a student reported direct observation by a resident preceptor. Conclusions: eCEX appears to be an effective means of enhancing student evaluation.